Identification and expression of a stearoyl-ACP desaturase gene responsible for oleic acid accumulation in Xanthoceras sorbifolia seeds - Zhao, Na (Plant physiology and biochemistry : PPB, 2015)
Copyright © 2014 Elsevier Masson SAS. All rights reserved.